A numerical structural analysis of ducted, high-solidity, fibre-composite tidal turbine rotor configurations in real flow conditions. (1st August 2021) - Borg, Mitchell G.; Xiao, Qing; Allsop, Steven; Incecik, Atilla; Peyrard, Christophe
Abstract: Establishing a design and material evaluation of unique tidal turbine rotors in true hydrodynamic conditions by means of a numerical structural analysis has presented inadequacies in implementing spatial and temporal loading along the blade surfaces. This study puts forward a structural performance investigation of true-scale, ducted, high-solidity, fibre-composite tidal turbine rotor configurations in aligned and yawed flows by utilising outputs from unsteady blade-resolved computational fluid dynamic models as boundary condition loads within a finite-element numerical model. In implementation of the partitioned-approach fluid–structure interaction procedure, three distinct internal blade designs were analysed. Investigating criteria related to structural deformation and induced strains, hydrostatic & hydrodynamic analyses are put forward in representation of the rotor within the flow conditions at the installation depth. The resultant axial deflections for the proposed designs describe a maximum deflection-to-bladespan ratio of 0.04, inducing a maximum strain of 0.9%. A fatigue response analysis is undertaken to acknowledge the blade material properties required to prevent temporal failure. Highlights: A blade-resolved partitioned-approach fluid–structure interaction analysis of a ducted high-solidity rotor. Imports static pressure and wall shear-stress data from unsteady blade-resolved CFD. Analyses distinct fibre-composite internal blade designs to establish the structural response. Conducts fatigue investigations in relation to the induced hydrodynamic temporal loads.